Characterization of a new epidemic necrotic pyoderma in fur animals and its association with Arcanobacterium phocae infection. - Heli Nordgren; Kirsi Aaltonen; Tarja Sironen; Paula M Kinnunen; Ilkka Kivistö; Mirja Raunio-Saarnisto; Anna-Maria Moisander-Jylhä; Johanna Korpela; Ulla-Maija Kokkonen; Udo Hetzel; Antti Sukura; Olli Vapalahti (PLoS ONE, 2014)
A new type of pyoderma was detected in Finnish fur animals in 2007. The disease continues to spread within and between farms, with severe and potentially fatal symptoms. It compromises animal welfare and causes considerable economic losses to farmers. A case-control study was performed in 2010-2011 to describe the entity and to identify the causative agent. Altogether 99 fur animals were necropsied followed by pathological and microbiological examination. The data indicated that the disease clinically manifests in mink (Neovison vison) by necrotic dermatitis of the feet and facial skin. In finnraccoons (Nyctereutes procyonoides), it causes painful abscesses in the paws. Foxes (Vulpes lagopus) are affected by severe conjunctivitis and the infection rapidly spreads to the eyelids and facial skin. A common finding at necropsy was necrotic pyoderma. Microbiological analysis revealed the presence of a number of potential causative agents, including a novel Streptococcus sp. The common finding from all diseased animals of all species was Arcanobacterium phocae. This bacterium has previously been isolated from marine mammals with skin lesions but this is the first report of A. phocae isolated in fur animals with pyoderma. The results obtained from this study implicate A. phocae as a potential causative pathogen of fur animal epidemic necrotic pyoderma (FENP) and support observations that the epidemic may have originated in a species-shift of the causative agent from marine mammals. The variable disease pattern and the presence of other infectious agents (in particular the novel Streptococcus sp.) suggest a multifactorial etiology for FENP, and further studies are needed to determine the environmental, immunological and infectious factors contributing to the disease.